Law-Centric Online Business and Social Media Data - Kurniawati, Dilla Haniah; Mediawati, Noor Fatimah; Masudin, Noor (Proceedings of The ICECRS, 2023)
This article presents a curated dataset sourced from Lens.org, encompassing 3,075 articles from journals and conference proceedings centered on law, online business, and social media. The dataset aims to support digital forensic investigations in these realms. Accessible in CSV and BIBTEX formats, retrieved on November 22, 2022, this collection facilitates literature reviews and future studies, offering a resourceful pool for researchers exploring the intersection of online business and social media. The dataset stands as a valuable asset for experimentation and analysis, aiding scholars seeking comprehensive insights in these domains.Highlights : Legal Focus: Dataset comprising 3,075 articles centered on law, online business, and social media. Research Support: Facilitates digital forensic investigations in the realms of online business and social media. Resource Accessibility: Exported in CSV and BIBTEX formats for literature reviews, aiding future studies and analysis. Keywords:Data Collection, Digital Forensics, Online Business, Social Media, Law-Centric Research